Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0031638
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Cell Imaging and Manipulation Using Conventional Halogen Lamp Microscopy

Abstract: Technologies for vitally labeling cells with fluorescent dyes have advanced remarkably. However, to excite fluorescent dyes currently requires powerful illumination, which can cause phototoxic damage to the cells and increases the cost of microscopy. We have developed a filter system to excite fluorescent dyes using a conventional transmission microscope equipped with a halogen lamp. This method allows us to observe previously invisible cell organelles, such as the metaphase spindle of oocytes, without causing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…It has been reported that phosphorylation of histone H3S10 occurs specifically in chromosomes of somatic cells and oocytes at the metaphase stage (Bui et al 2004;Swain et al 2007;Van Hooser et al 1998;Wei et al 1998). Recently, we demonstrated that the metaphase plate of the second meiotic division in mouse and cattle oocytes is clearly visible after injection of an antibody under a halogen-lamp microscope (Yamagata et al, 2012).…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…It has been reported that phosphorylation of histone H3S10 occurs specifically in chromosomes of somatic cells and oocytes at the metaphase stage (Bui et al 2004;Swain et al 2007;Van Hooser et al 1998;Wei et al 1998). Recently, we demonstrated that the metaphase plate of the second meiotic division in mouse and cattle oocytes is clearly visible after injection of an antibody under a halogen-lamp microscope (Yamagata et al, 2012).…”
Section: Introductionmentioning
confidence: 60%
“…The microscope setup with a transmission fluorescence filter system used for manipulation and observation was described previously (Yamagata et al, 2012). Briefly, an inverted microscope (IX-70, Olympus, Tokyo, Japan) equipped with a 100 W halogen lamp was used for manipulation and observation.…”
Section: Setup Of Microscope With a Transmission Fluorescence Filter mentioning
confidence: 99%
See 1 more Smart Citation
“…The alternatives to canonical (OH/UV) enucleation proposed so far are: (1) Polarized light microscopy, that locates the metaphase spindle (Liu et al, 2000); (2) the use of softer filter systems with traditional halogen lamps, associated with fluorescent antibody directed against the phosphorylated serine 10 of histone H3 (H3S10ph) binding to M-phase chromosomes (Yamagata et al, 2012); and (3) DAE (Yin et al, 2002).…”
mentioning
confidence: 99%
“…The use of polarized light in large animal oocytes is less advisable due to the high lipid droplet content. The softer halogen lamp associated with fluorescent antibody anti-histone to locate the chromosomes reduces the phototoxic effects but adds the further step of antibody injection prior to enucleation (Yamagata et al, 2012), hence it is unpractical.…”
mentioning
confidence: 99%